2003
DOI: 10.1126/science.1082710
|View full text |Cite
|
Sign up to set email alerts
|

The Pentacovalent Phosphorus Intermediate of a Phosphoryl Transfer Reaction

Abstract: Enzymes provide enormous rate enhancements, unmatched by any other type of catalyst. The stabilization of high-energy states along the reaction coordinate is the crux of the catalytic power of enzymes. We report the atomic-resolution structure of a high-energy reaction intermediate stabilized in the active site of an enzyme. Crystallization of phosphorylated beta-phosphoglucomutase in the presence of the Mg(II) cofactor and either of the substrates glucose 1-phosphate or glucose 6-phosphate produced crystals o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
272
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 318 publications
(291 citation statements)
references
References 42 publications
18
272
1
Order By: Relevance
“…Thus, by analogy, the aspartate would be in the correct position relative to the phosphorylated substrate for in-line nucleophilic attack at the phosphorus atom. This arrangement of ligands to WO 4 2-closely mirrors that found in the structures of WO 4 2--bound phosphonatase (PDB entry 1FEZ) (6), phosphate-bound phosphoserine phosphatase (PDB entry 1F5S) (7), glucose 1,6-(bis)phosphate-bound -PGM (PDB entry 1O03) (30), and phosphate-bound human mitochondrial deoxyribonucleotidase (PDB entry 1MH9) (31). The loop I amide nitrogen interactions are all retained as well as the loop II hydroxyl group of serine or threonine.…”
Section: Mg(ii) and Phosphate-binding Residues Of The Active Sitesupporting
confidence: 64%
“…Thus, by analogy, the aspartate would be in the correct position relative to the phosphorylated substrate for in-line nucleophilic attack at the phosphorus atom. This arrangement of ligands to WO 4 2-closely mirrors that found in the structures of WO 4 2--bound phosphonatase (PDB entry 1FEZ) (6), phosphate-bound phosphoserine phosphatase (PDB entry 1F5S) (7), glucose 1,6-(bis)phosphate-bound -PGM (PDB entry 1O03) (30), and phosphate-bound human mitochondrial deoxyribonucleotidase (PDB entry 1MH9) (31). The loop I amide nitrogen interactions are all retained as well as the loop II hydroxyl group of serine or threonine.…”
Section: Mg(ii) and Phosphate-binding Residues Of The Active Sitesupporting
confidence: 64%
“…20 Stable five-coordinate oxovanadium species are a suitable mimic for the five-coordinate phosphoryl transition state proposed for a number of phosphorolytic reactions. 30,31 Previously, it was reported that the inhibition constant of pig PAP for vanadate is 40 μmol L -1 at pH 5.5, and the mode of binding of the inhibitor is noncompetitive. 23 The di-zinc alkaline phosphatase from Escherichia coli is inhibited by vanadate with similar efficiency (K i = 12 μmol L -1 at pH 8.0), and the crystal structure of the enzyme-inhibitor complex shows that vanadate binds in a penta-coordinate geometry to the active site with three of its oxygen atoms coordinating the two metal ions in the active site in a tripodal arrangement (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…The rate and equilibrium for phosphorylation of the active site Asp8 by G16bisP are examined. A model for PGM catalysis is proposed that is based on cycling of the enzyme between the open and closed conformations observed in the reported PGM X-ray crystal structures (6,(12)(13)(14). lactis -phosphoglucomutase ( PGM) was prepared according to a published procedure (16).…”
mentioning
confidence: 99%